2010
DOI: 10.1080/03949370903515919
|View full text |Cite
|
Sign up to set email alerts
|

Variation of genetic and behavioural traits in the sandhopperTalitrus saltator(Crustacea Amphipoda) along a dynamic sand beach

Abstract: In an attempt to unravel the possible relationships among coastal stability, genetic variability and orientation behaviour in the sandhopper Talitrus saltator, we have screened four subpopulations of this species. Sandhoppers along 3 km of a dynamic sand beach were studied for orientation performance (i.e. adherence to the seaward theoretical escape direction (TED)) and sequence variation for a fragment of the mitochondrial (mt) gene encoding for the cytochrome oxidase subunit I (COI). The sampling sites diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…We screened sequence of mtDNA coding for a fragment of cytochrome C oxidase subunit I (COI). This gene has been proven informative at the interspecific and intraspecific levels in crustacean (Henzler 2006;Kelly et al 2006;Ketmaier et al 2010;Pavesi et al 2011;Young et al 2012). More specifically, first we tested whether the geographical isolation of lakes and ponds will prevent gene flow or not, and second we constructed the phylogeographical relationships of the subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…We screened sequence of mtDNA coding for a fragment of cytochrome C oxidase subunit I (COI). This gene has been proven informative at the interspecific and intraspecific levels in crustacean (Henzler 2006;Kelly et al 2006;Ketmaier et al 2010;Pavesi et al 2011;Young et al 2012). More specifically, first we tested whether the geographical isolation of lakes and ponds will prevent gene flow or not, and second we constructed the phylogeographical relationships of the subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…Being a behavioural feature, orientation represents one of the first responses to the environmental variations, and the time-scale in this case is small, consisting of a few months (within an individual's life span). On the Collelungo beach Talitrus saltator is the dominant species, so its behaviour must be well adapted to its life-environment, as documented in similar studies carried out in 2002-2003 on this beach (Scapini et al, 2005b;Ketmaier et al, 2010). The existence of previous data also offered the possibility of comparing results from before and after the intervention for the mitigation of the beach erosion process, and check the suitability of sandhoppers' orientation as an impact's bioindicator.…”
Section: Discussionmentioning
confidence: 92%
“…Barsanti et al, 2011, regarding Italian coasts). Later studies led however to similar conclusions: differences in orientation precision toward the shoreline were shown by populations from different points along the same continuous beach on the Tyrrhenian coasts of Italy, subject to different erosion/accretion dynamics (Scapini et al, 2005;Ketmaier et al, 2010). Also Bouslama et al (2011) found a link between talitrid behaviour and environmental stability on two beaches of the Tunisian coasts comparing behavioural traits (orientation and locomotor activity rhythms).…”
Section: Talitrids: Fine Tuning To a Changing Environmentmentioning
confidence: 86%